2020
DOI: 10.1002/for.2678
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Australia's real house price index: A comparison of time series and machine learning methods

Abstract: We employ 47 different algorithms to forecast Australian log real house prices and growth rates, and compare their ability to produce accurate out-of-sample predictions. The algorithms, which are specified in both singleand multi-equation frameworks, consist of traditional time series models, machine learning (ML) procedures, and deep learning neural networks. A method is adopted to compute iterated multistep forecasts from nonlinear ML specifications. While the rankings of forecast accuracy depend on the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Ng (2014), Döpke et al (2017), and Medeiros et al (2019) improve forecast accuracy with random forests and boosting, while Yousuf and Ng (2019) use boosting for high-dimensional predictive regressions with time varying parameters. Others compare machine learning methods in horse races (Ahmed et al, 2010;Chen et al, 2019;Kim & Swanson, 2018;Li & Chen, 2014;Milunovich, 2020;Smeekes & Wijler, 2018;Stock & Watson, 2012b). Works such as Joseph (2019) and Zhao and Hastie (2019) contribute to the interpretability of a given model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ng (2014), Döpke et al (2017), and Medeiros et al (2019) improve forecast accuracy with random forests and boosting, while Yousuf and Ng (2019) use boosting for high-dimensional predictive regressions with time varying parameters. Others compare machine learning methods in horse races (Ahmed et al, 2010;Chen et al, 2019;Kim & Swanson, 2018;Li & Chen, 2014;Milunovich, 2020;Smeekes & Wijler, 2018;Stock & Watson, 2012b). Works such as Joseph (2019) and Zhao and Hastie (2019) contribute to the interpretability of a given model.…”
Section: Introductionmentioning
confidence: 99%
“…Ng (2014), Döpke et al (2017) and Medeiros et al (2019) improve forecast accuracy with random forests and boosting, while Yousuf and Ng (2019) use boosting for high-dimensional predictive regressions with time varying parameters. Others compare machine learning methods in horse races (Ahmed et al, 2010;Stock and Watson, 2012b;Li and Chen, 2014;Kim and Swanson, 2018;Smeekes and Wijler, 2018;Chen et al, 2019;Milunovich, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…7 A related literature considers the ability of machine learning and time series models to forecast house prices. See, e.g., Milunovich (2020 Little prior work uses the highly geographically disaggregated Australian data adopted in the current paper to study heterogeneous effects across housing markets. However, La Cava and He (2021) makes progress in this direction.…”
Section: (I) Related Literaturementioning
confidence: 99%
“…Results of numerous empirical studies have shown that ML approaches outperform time series models in forecasting different financial assets [ 13 ]. A comparative analysis of statistical models and machine learning techniques can be found in [ 14 ]. Among the ML techniques, Artificial Neural Network (ANN), Generalized Neural Network (GRNN), Support Vector Regression (SVR), Random Forest (RF) and Gradient Boosting Machine (GBM) etc.…”
Section: Introductionmentioning
confidence: 99%